In vitro activity of fludalanine combined with pentizidone compared with those of other agents. - Wise, R (1984)
The in vitro activity of fludalanine ( MK641 ) combined with pentizidone ( MK642 ) so as to give a fludalanine /D-cycloserine ratio of 1:1 was compared with the activities of ampicillin, ticarcillin, cefuroxime, ceftazidime, and trimethoprim against 452 recent isolates and known beta-lactam- and trimethoprim-resistant strains. In addition, the in vitro activity of fludalanine - pentizidone on four different media, including a defined medium ( DFN -2), was studied. The MIC of fludalanine - pentizidone against 90% of Escherichia coli, Klebsiella spp., Enterobacter spp., Providencia stuartii, Haemophilus influenzae, Neisseria gonorrhoeae, Staphylococcus aureus, and fecal streptococci was 4 micrograms or less per ml on DFN -2, and activity was somewhat reduced on the other media. Proteus spp. and Pseudomonas aeruginosa (90% MIC, less than or equal to 64 micrograms/ml) and Bacteroides spp. (90% MIC, 16 micrograms/ml) were less susceptible. Generally, fludalanine - pentizidone was less active than ceftazidime and comparable in activity to cefuroxime. beta-Lactamase-producing and trimethoprim-resistant strains tended to be susceptible to fludalanine - pentidizone . In the absence of human serum, the MBC of fludalanine - pentizidone was similar to the MIC. In the presence of increasing concentrations of human serum, there tended to be a greater difference between the MIC and MBC.